(untitled) (The International Journal for Scientific Research, 2025)
Objectives: The research aims to show the impact of the Qur’an and language on Ibn Arabi’s political thought. Some researchers may have looked at Ibn Arabi in a negative light due to his belonging to this school, so the research seeks to show his political thought and his adherence to the Qur’an and language in his own way Methodology: The research followed the inductive, descriptive, and analytical approach to arrive at Ibn Arabi’s political views and the impact of the Qur’an and language on them. Results: It was revealed through this study that Ibn Arabi is considered one of the founders of the mystical doctrine, and despite that he had strong contributions in this field that appeared through his mystical meditations and the attempt to link the sensory and the rational and the apparent and the hidden. It was also shown that his mystical meditations emanated from the Holy Qur’an. And he dealt with the Qur’an with two levels of understanding, one of which appears in the apparent language and the other in interpretation. Conclusion: This study attempted to provide a detailed analysis of Ibn Arabi’s political views through his writings, and to explore the impact of the Qur’an and language on his political thought.